Association between prenatal exposure to bisphenols and preterm birth: the interaction effect of anemia - Ya-ling Li; Hong-yu Mao; Lu-ming Yan; Zi-yi Liu; Shu Sun; Ting-ting Jiang; Le-yan Xu; Xin-yi Zhang; Bo-lin Liu; Min Zhu; Ji-an Xie; Jia-hu Hao; et al. (Environment International)
Maternal exposure to bisphenols (BPs) during pregnancy may negatively impact birth outcomes. However, research on the interaction between anemia and exposure in relation to preterm birth (PTB) is limited. A prospective birth cohort was used to assess the relationship between prenatal exposure to BPs and PTB, and to explore potential effect modification by maternal anemia. The maternal urine samples were collected during each trimester to measure BPs concentrations. The associations between individual BPs and PTB were assessed using generalized linear model (GLM). Generalized estimating equations (GEEs) identified critical exposure windows. Multiple statistical methods—including quantile g-computation (q-gcomp), weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR)—were employed to evaluate cumulative and mixture effects. Interaction analyses on both additive and multiplicative scales were performed for selected BPs linked to PTB and time windows of maternal anemia sensitivity. Significant associations were observed between BPs exposure and PTB, particularly for BPAF and BPP in early pregnancy (OR = 1.222, 95 % CI: 1.006–1.486 and OR = 1.454, 95 % CI: 1.054–2.007), and for BPB in both mid (OR = 1.651) and late pregnancy (OR = 1.952). GEEs confirmed early and late pregnancy as critical windows. Cumulative exposure analyses indicated that higher BPs levels in these periods significantly increased PTB odds. Significant additive and multiplicative interactions were identified between the third trimester BPB exposure and maternal anemia, suggesting a potential synergistic effect on PTB. The study found that prenatal exposure to specific BPs is significantly associated with increased risk of PTB, with critical exposure windows identified in early and late pregnancy, and reveals that maternal anemia may amplify these effects through synergistic interactions.